Photothermal-promoted multi-functional dual network polysaccharide hydrogel adhesive for infected and susceptible wound healing. (1st December 2021) - Chen, Chonghao; Zhou, Ping; Huang, Chi; Zeng, Rui; Yang, Ling; Han, Zhen; Qu, Yan; Zhang, Chen
Abstract: A low-cost wound dressing with efficient sterilization and exhibiting long-term antimicrobial activity is required for the absence of antibiotics, particularly for the wound healing of patients with chronic wounds or long-term activities under low sanitary conditions (e.g., battlefield and poverty-stricken areas). Here, a dual dynamic crosslinking hydrogel was introduced. The hydrogel was supported by gallic acid grafted chitosan and oxidized Bletilla striata polysaccharide as the scaffold and formed by two types of dynamic crosslinking: Schiff base, pyrogallol-Fe 3+ . It exhibited its adhesion, self-healing, good biocompatibility, great intrinsic antibacterial, and near-infrared photothermal conversion activity. In addition, the use of two types of polysaccharides, and the existence of the photothermal effect, making the hydrogel has the functions of accelerating gelation, degradation on-demand, and rapid sterilization. In brief, such cost-effective multifunctional hydrogel could support wound healing in patients prone to bacterial infection, and it has a promising application in the care of infected wounds. Graphical abstract: Unlabelled Image